RhoA wild-type allele loss unleashes the cancer driver function of RhoA E40Q - Justine Noujarède; Qiuyue Wang; Eleftherios Panagiotis Kokkinogenis; Yuewan Luo; Ivona Cudina; Simon Willaume; Clémence Mooser; Lap Phuoc Nguyen; Mads Frederik Poulsen; Simon Heijmerikx; Thu Han Le Phan; Xiubin He; et al. (Journal of Clinical Investigation, 2026)
Cancer hotspot mutations of unknown function often obscure the functional understanding of the molecular pathways underlying cancer formation and limit precision medicine progress. Here, we investigated unresolved driver functions of RHOA in head and neck squamous cell carcinoma (HNSCC). Our investigation reveals that RHOA E40Q is a partial loss-of-function allele which paradoxically promotes tumorigenesis only in the absence of wild-type RhoA. Therefore, mice expressing RHOA E40Q specifically in keratinocytes lacking wild-type RhoA spontaneously developed squamous cell carcinoma and showed defective hair shaft formation. Mechanistically, this is related to increased replication stress and genome instability caused by aberrant expression of cell cycle regulators and DNA repair genes, independent of the classical RhoA effectors ROCK and DIAPH. These data establish RHOA E40Q as an unusual, context-dependent oncogenic driver: a seemingly inactive variant that unleashes its tumor-promoting potential only when the wild-type allele is absent.